Corrigendum to: “Heavy-tailed value-at-risk analysis for Malaysian Stock exchange” [Physica A 387 (2008) 4285–4298] - CHEONG, C (ELSEVIER SCIENCE BV, 2008)
Heavy-tailed value-at-risk analysis for Malaysian Stock exchange